2020
DOI: 10.1162/dint_a_00032
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Analytics on Sensitive Medical Data: The Personal Health Train

Abstract: In recent years, as newer technologies have evolved around the healthcare ecosystem, more and more data have been generated. Advanced analytics could power the data collected from numerous sources, both from healthcare institutions, or generated by individuals themselves via apps and devices, and lead to innovations in treatment and diagnosis of diseases; improve the care given to the patient; and empower citizens to participate in the decision-making process regarding their own health and well-being. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 15 publications
0
97
0
3
Order By: Relevance
“…Distributed data analytics utilizes the data at the original location, can interact with the data, and complete their task without giving access to the end-user. In contrast to other approaches, it is technology agnostic and aims at maximum interoperability between diverse systems, by focusing on machine-readable and interpretable data, metadata, workflows, and services [25] ( Table 1).…”
Section: Infrastructure and Interoperabilitymentioning
confidence: 99%
“…Distributed data analytics utilizes the data at the original location, can interact with the data, and complete their task without giving access to the end-user. In contrast to other approaches, it is technology agnostic and aims at maximum interoperability between diverse systems, by focusing on machine-readable and interpretable data, metadata, workflows, and services [25] ( Table 1).…”
Section: Infrastructure and Interoperabilitymentioning
confidence: 99%
“…The results of the queries or analyses are aggregated and returned to the researcher who submitted the query. A federated data system enabling linkage and analysis of sensitive health care data in multiple repositories is proposed by the European Personal Health Train, where analytical tasks visit data sources [ 24 ]. Data sets are likened to stations , algorithms are likened to the payload delivered by a train , and the network is likened to the train track .…”
Section: Scalability Of Model-to-data To a Network Of Multiple Resourmentioning
confidence: 99%
“…The FAIRness of analysis workflows is also increasingly key for the reproducibility of data-intensive health research. In the context of model-to-data, this FAIRness may additionally be essential for trust between data users and data stewards [ 24 , 47 ]. Data stewards need to possess not only traditional data governance expertise but also significant computational and analysis skills, a rare combination, and one without formally recognized qualifications at this time.…”
Section: Data Sharing Incentives and Sustainabilitymentioning
confidence: 99%
“…Beyan et al [ 12 ] have shown that an enormous amount of usable health data is currently imprisoned inside the organizational territories of hospitals, clinics, and within patients’ devices due to ethical concerns and data protection rules. However, data reuse, even if secondary to data collection and first analysis, may drive more extensive and valuable new research directions than intended for the primary purpose [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…France has also launched the Health Data Hub with similar aims [ 15 ]. Currently, researchers and stakeholders are working on infrastructure to support distributed and federated solutions to make the data, software, or digital objects smart in their original silos [ 12 ]. Europe would benefit from an integrated infrastructure in which data and computing services for big data can be easily shared and reused, and plans are underway to establish the Europe Research Area for this purpose [ 16 ].…”
Section: Introductionmentioning
confidence: 99%